Regimen of procarbazine, lomustine, and vincristine versus temozolomide for gliomas - Wick, Wolfgang; Winkler, Frank (Cancer, 2018)
Both temozolomide and the regimen of procarbazine, lomustine, and vincristine (PCV) prolong survival in patients with malignant gliomas when used as an adjuvant to radiotherapy (temozolomide in patients with newly diagnosed glioblastoma and 1p/19q non-codeleted anaplastic gliomas and PCV in both those patients with newly diagnosed high-risk low-grade gliomas and those with 1p/19q codeleted anaplastic oligodendrogliomas). However, there is debate regarding the appropriate alkylating regimen to use for individuals with glial neoplasms. Balancing survival advantages versus risks of toxicity and impact on quality of life are important elements of this debate.